Insights About Stabilization of Sulforaphane Through Microencapsulation - Bustos-Cerda, R; Mahn-Osses, A; Zambrano-Ibarra, V (Elsevier Ltd, 2019)
The health–promoting properties of sulforaphane (SFN) are well known, however its instability is still a hurdle for its incorporation into food matrices. SFN can be stabilized by microencapsulation, technique sparingly explored for isothiocyanates so far. This review summarizes the advances in microencapsulation of SFN and other isothiocyanates. Encapsulation efficiency and degradation rate of sulforaphane in different systems are compared and discussed. Ionic gelation and complex coacervation seem more adequate for SFN, both underexplored until now. Drying conditions after chemical encapsulation are determinant, most likely related to thermal degradation of SFN. The current information is insufficient to identify the most adequate encapsulation system and the optimal process conditions to stabilize SFN aiming at its incorporation into food matrices. Accordingly, encapsulation conditions should be investigated, which arises as a new research line. Stability studies are encouraged since this information will help in designing SFN microencapsulation strategies that extend the industrial application of this promising health-promoting compound. © 2019 The Authors